New politics and satire: the Euro financial crisis and the one-finger salute. Issue 7 (3rd July 2017) - Bessant, Judith
ABSTRACT: This article argues that the conventional conceptualization in political science of politics is problematic, that it is overly narrow and constrained. This is because it excludes a range of actions like satire and humour which have come to play an increasing role in inspiring and provoking powerful political emotions and in informing the political agenda. Drawing on the work of critical scholars, it is argued that emotion, ethics and art can be deeply political. Moreover, new forms of media have encouraged new–old forms of political action often at the hands of young people who hitherto have been marginalized from the public sphere. Digital technology enables the production of user-generated content, opening new spaces for information, the exchange of ideas and mobilization. This article highlights the work of the young German satirist Jan Böhmermann to demonstrate how expressive art is playing a major role in shaping public opinion, in contesting power elites and informing political debate. In short, I use Böhmermann's 2015 satire depicting Greco-German relations in the midst of a financial crisis and fears of loan defaults to argue for a broader understanding of politics that is inclusive of activities conventionally deemed non-rational.